Hypertension, Periodontal Disease, and Potassium Intake in Nonsmoking, Nondrinker African Women on No Medication - Masashi Yamori; Marina Njelekela; Jacob Mtabaji; Yukio Yamori; Kazuhisa Bessho (International Journal of Hypertension)
The purpose of this cross-sectional study was to investigate the association of periodontitis and/or tooth loss with hypertension by excluding the common confounders. Eighty-one Tanzanian women who were aged 46–58 years, nonsmokers, nonalcoholic drinkers, and on no medication underwent clinical examination. Multiple-regression analysis showed that the severity of periodontitis was significantly correlated with increased systolic blood pressure and diastolic blood pressure. Simple-regression analysis indicated that the severity of periodontitis was inversely correlated with 24-hour urinary excretion of potassium (r=-0.579, P=0.0004) and also inversely with the frequency of intakes of green vegetables (r=-0.232, P=0.031) and fruits (r=-0.217, P=0.0043). Low-potassium intake in the diet mostly accompanied by low dietary fiber intake increases BP as well as periodontal inflammation. Potassium intake may be an important factor linking periodontitis and hypertension in middle-aged nonsmoking and nonalcoholic women on no medication, although chronic inflammation such as periodontitis may cause hypertension through a more direct mechanism.